Seasonal occurrence of Lygus bugs on field crops in Finland - Anna-Liisa Varis (Agricultural and Food Science, 1997)
A long term survey of Lygus populations (Heteroptera, Miridae) was carried out on eight arable crops in southern Finland. Sweep net samples were taken weekly during the growing season in 16 successive years. The hibernated adults first appeared in May on overwintered crops: winter rye, red clover-timothy ley and winter turnip rape. Turnip rape and ley harbored the most Lygus adults until the end of June even if some of them started to move to spring cereals (wheat, oats and barley), potato and sugarbeet after the emergence of these plants. The numbers of adults on cereals remained small until the crops reached the heading stage. The peak occurred in the first half of August. The adult numbers on potato and sugarbeet were also highest in August. The total number of adults was highest on wheat. Nymphs were found on all the studied crops. They were first captured in the second half of June and reached a peak between mid-July and mid-August. Numbers were highest on wheat. The most common species on all crops was L. rugulipennis Poppius, constituting 92% of the adults. The other Lygus species were L. gemellatus (Herrich-Schaeffer), L. pratensis (L.) and L. punctatus (Zetterstedt). A few specimens of L. wagneri Remane were also found.